Optimizing Human Resources in Higher Education Institutions: Strategies and Challenges - Azis, Nur; Sundoro, Aries; Wulandari, Wulandari; Novi Irwansyah; Choerul Fakih (Liquidity, 2026)
Effective human resource (HR) management is a cornerstone for enhancing the quality of higher education institutions. Optimizing HR extends beyond enhancing the competencies of faculty and staff to include strengthening managerial systems, fostering workplace motivation, and leveraging information technology. This study aims to identify effective strategies for HR optimization in universities and explore the challenges encountered during implementation. Employing a descriptive qualitative literature review, the findings reveal that sustainable professional development, merit-based recruitment and promotion, and nurturing a culture of collaboration are most impactful. However, significant obstacles include limited financial resources, resistance to organizational change, and a lack of awareness of the importance of strategic HR management. To ensure sustainable improvement in educational quality, institutional commitment and supportive policies are essential.